Determinan Perilaku Merokok Mahasiswa di Universitas Jambi - Winner MS; M. Ridwan; Usi Lanita (Lembaga Pengembangan Kinerja Dosen, 2025)
According to WHO data from 2020, the number of smokers worldwide reached 22.3% of the global population aged over 15 years. Based on the 2023 Indonesian Health Survey, Jambi Province has a relatively high smoking rate, with daily smokers accounting for 16.8% of the population. This study is a quantitative research using a cross-sectional approach. The study population consisted of active male undergraduate students at the University of Jambi who were active smokers in semesters 2 to 8. A total of 379 respondents were selected using proportional random sampling. Data were analyzed using univariate, bivariate, and multivariate methods. The prevalence of heavy smokers among students at the University of Jambi was 6.9%. A significant association was found between knowledge level and smoking behavior, with an odds ratio (OR) of 3.204 (95% CI: 1.31–7.81). Multivariate analysis revealed that knowledge was the most influential variable affecting smoking behavior, with an adjusted odds ratio (AOR) of 3.447 (95% CI: 1.357–8.757). This result was statistically significant (p-value = 0.011) after controlling for attitude and knowledge of smoke-free areas (Kawasan Tanpa Rokok, KTR). There is a significant relationship between knowledge and smoking behavior. However, there is no relationship between attitude, peer influence, and compliance with smoke-free regulations and conventional smoking behavior.